Parlament Europejski wobec reformy systemu instytucjonalnego w trakcie obrad Konwentu w sprawie przyszłości Europy - Kozub, Patrycja (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
The article is a reconstruction of the position of the European Parliament and its delegates to the Convention on the Future of Europe towards the greatest institutional reform of the European Union in the history of European integration. The author analyzes the impact of the European Parliament on the provisions of the draft Constitutional Treaty, concerning, among other things: the axiology of the Union, the institutional system, the role of national parliaments and enhanced cooperation. These studies made it possible to observe that the European Parliament, like the European Commission, was one of the Community institutions which was particularly interested in strengthening the transnational factor in the process of European integration, including the European Union’s institutional system. Therefore, during the debate, the representatives of the European Parliament stated their demands for: further enlargement of the powers of Parliament in the legislative process, changes in decision-making procedures in the Council of the European Union, as well as strengthening the position of the European Commission in the European Union’s institutional system. Analysis showed that this position was the consensus worked out from the varied opinions of European political groups, which were presented by individual members of the European Parliament involved in the institutional issues
The European Parliament’s attitude towards reform of the institutional system during the Convention on the Future of Europe